(untitled) (Revista Brasileira de Ciências Farmacêuticas, 2007)
Microparticulate systems of nimesulide (NIM) were prepared by modified solvent evaporation method using different variables such as polymer: drug (NIM) ratios (cellulose acetate, CA: nimesulide, NIM) (1:9, 1:6 and 1:3), agitation speeds (500-1500 rpm) and stirring time (15-30 min). The effects of processing variables were evaluated by microparticle size and entrapment efficiency. The average microparticle size increases from 66.8±1.45 to 87.3±1.06 µm with increase in the polymer concentration while reduces with increase in agitation speed and stirring time; but at the too higher speed gives irregular shape of particles. The highest entrapment efficiency (77.83±0.51%), size uniformity, free flowability, i.e., angle of repose (23.5±0.4º) and compressibility index (14.2±0.6%), of microparticles were found with 1:6 (polymer: drug ratio), at 1000 rpm and 20 min stirring time among all prepared microparticles (P < 0.05). The in-vitro drug release study of microparticles with optimized processing variables (agitation speed and time) were carried out and compared with conventional and marketed SR tablets. The conventional tablet releases maximum drug within 4 h while microparticulate system releases more than 14 h. All formulations followed first order release kinetic and diffusion controlled drug release (Higuchi model). These microparticles are stable at room temperature (25±1 °C) but agglomerate at elevated temperature (50±1 °C) by softening and fusion of the polymer observed under SEM study.